(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Heavy metals have a relatively high density and occur naturally in the environment or introduced by anthropogenic activities. They may be essential or non-essential to living organisms causing toxicity, environmental pollution or contaminate food chain. This research determined the hazard from ingestion of Moringa Oleifera leaves cultivated along River Ginzo, Katsina through the Estimation of Daily Intake of Metals (EDIM), Target Hazard Quotient/Hazard Index (THQ/HI) and Incremental Lifetime Cancer Risk (ILCR) from exposure to Co, Cu Pb and Ni in the leave samples obtained by random sampling. Heavy metals in samples were determined using Atomic Absorption Spectrophotometry (AAS) and analysed using Social Package for Social Science. The Result showed that levels of Co in all samples exceeded the 0.05ppm permissible limit in irrigation water. Values of Pb, Ni, and Cu and Ni in all soil samples exceeded the 0.05ppm, 0.30ppm and 0.05ppm USEPA, 2000 acceptable limits. Concentration of metals in leave samples are within the WHO/FAO 2014 acceptable limits. EDIM in M. oliefera were below tolerable daily intake, implying no health risk. THQ/HI for both essential and non-essential elements in leave samples were >1, implying no health hazard. ILCR showed potential risk of contracting cancer from the consumption of M. oleifera leaves grown in the study areas as Incremental Lifetime Cancer Risk values exceed the acceptable and negligible range of 10-4-10-6particularly of Ni (2.23E-2). As a result, measures should be put in place to prevent disposal of wastes containing heavy metals into River Ginzo used for irrigation purposes.